2021
DOI: 10.33546/bnj.1337
|View full text |Cite
|
Sign up to set email alerts
|

Symptom experience of adverse drug reaction among male and female patients with newly diagnosed pulmonary tuberculosis in Thailand

Abstract: Background: Patients with newly diagnosed pulmonary tuberculosis often suffer from adverse drug reaction symptoms, which leads to the automatic discontinuation of anti-tuberculosis drugs. Thus, understanding symptom experience of adverse drug reactions is necessary.Objective: This study aimed to examine differences in symptoms experienced in four dimensions: presence, frequency, severity, and distress of adverse drug reactions, between male and female patients.Methods: This was a quantitative survey with a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
2
0
2
Order By: Relevance
“… 18 , 19 Although TB is more commonly diagnosed in males, and males are known to have more unfavourable treatment outcomes and higher mortality, 20 , 21 several studies suggest that drug intolerance is more commonly experienced by female patients. 22 , 23 We found that females were more likely to have intolerance to RIF, but there was no difference in treatment outcomes between males and females in our cohort, indicating that alternative treatment regimens could be constructed despite RIF-related adverse events in our population. We found no significant difference in treatment outcomes between RIF-tolerant and RIF-intolerant patients, although those who were unable to tolerate RIF had a significantly longer duration of therapy.…”
Section: Discussionmentioning
confidence: 59%
“… 18 , 19 Although TB is more commonly diagnosed in males, and males are known to have more unfavourable treatment outcomes and higher mortality, 20 , 21 several studies suggest that drug intolerance is more commonly experienced by female patients. 22 , 23 We found that females were more likely to have intolerance to RIF, but there was no difference in treatment outcomes between males and females in our cohort, indicating that alternative treatment regimens could be constructed despite RIF-related adverse events in our population. We found no significant difference in treatment outcomes between RIF-tolerant and RIF-intolerant patients, although those who were unable to tolerate RIF had a significantly longer duration of therapy.…”
Section: Discussionmentioning
confidence: 59%
“…Em relação às diferenças da ocorrência de efeitos adversos do tratamento anti-TB entre homens e mulheres, os homens relataram vivenciar mais efeitos adversos que as mulheres. Uma possível razão para esse risco aumentado seria a maior tendência masculina ao tabagismo, ao etilismo e à drogadição comparados à população feminina (Thontham & Polsook, 2021).…”
Section: Discussionunclassified
“…Em relação aos sintomas decorrentes dos efeitos colaterais, homens declararam maior acontecimento de prurido relacionado à colestase intra-hepática. Em mulheres, a hiperbilirrubinemia foi o efeito colateral mais relatado, estando associado sobretudo aos medicamentos isoniazida e rifampicina, os quais se relacionam com o possível desenvolvimento de lesão hepática (Thontham & Polsook, 2021). Uma explicação para essa maior ocorrência seria a menor taxa de depuração hepática, menor índice de massa magra e divergências na atividade da enzima citocromo P450 (CYP) da parcela feminina, em comparação aos homens (Raftery et al, 2018).…”
Section: Discussionunclassified
“…42 , 43 Male patients were more likely to encounter ADRs than female patients, because males were more susceptible to behavioral and social factors. 27 , 44 , 45 This resulted in an increase in transmission of disease.…”
Section: Discussionmentioning
confidence: 99%